D)g(x) = 3^−x
Step-by-step explanationgiven the function
![f(x)=3^x](https://img.qammunity.org/2023/formulas/mathematics/high-school/jbadg032998mw28cc0i5bu61syxvy0x8dw.png)
it has a transformatio functio g(x), by checking the graph we can conclude the transformation was a reflection across y-xis
so, we need to apply the rule for that kind of transformation
the rule to reflect a function across the y-axis is
(x,y)→(−x,y)
![(x,y)\Rightarrow(-x,y)](https://img.qammunity.org/2023/formulas/mathematics/college/i1ysqez8lv2tgl97qe0q9kj1zucffvdsl1.png)
therfore, we need to negate the x coordiante, hence
![f(x)=3^x\Rightarrow reflection\text{ acrros y axis}\Rightarrow g(x)=3^(-x)](https://img.qammunity.org/2023/formulas/mathematics/college/r147p795s75b1nmhyo74htwwb6xuzdg31f.png)
therefore, the answer is
D)g(x) = 3^−x
I hope this helps you